Адміністративно-правове регулювання фінансових та економічних відносин в Україні: особливості та напрямки вдосконалення - Музичук, О. М.; Muzychuk, O. M. (Форум права. - 2023. - № 3(76). - С. 30-36, 2023)
Визначено особливості та напрямки вдосконалення адміністративно-правового регулювання фінансових та економічних відносин в Україні. Новизна роботи міститься у пропозиції окремих новітніх підходів у сфері нормативно-правового регулювання та організаційно-управлінського забезпечення. Розкрито сутність адміністративно-правового регулювання та його елементів. Опрацьовано погляди вітчизняних і зарубіжних науковців щодо проблематики, виокремлено найбільш актуальні, зумовлені провідними тенденціями розвитку суспільства та науки особливості фінансових та економічних відносин. Відзначено наявні недоліки у сфері адміністративно-правового регулювання гуманітарної допомоги. На основі осмислених особливостей та позицій вітчизняних і зарубіжних дослідників сформовано пропозиції з вдосконалення адміністративно-правового регулювання фінансових та економічних відносин.

Problem statement. In the modern world, economic and financial activities play a significant role in a country's stability and development. However, the effective functioning of these spheres is impossible without proper administrative and legal regulation. The purpose of the article is to identify the peculiarities and directions for improving the administrative and legal regulation of financial and economic relations in Ukraine. Methods. The article employs expert analysis to obtain the opinions and conclusions of scholars and experts, especially in the field of financial and economic law, and the comparative legal method to determine similarities and differences in administrative and legal regulation of finance and economics. Results. It is noted that issues related to administrative and legal regulation of financial and economic relations carry strategic importance. The following most relevant features, driven by leading trends in society and science, are identified: restructuring the qualitative and quantitative composition of subjects of international political economy while preserving traditional subjects and religious forms of regulation in certain countries, and the formation of an open finance system. Conclusions. The relevance of establishing relevant units (departments, offices, divisions, etc.) within state authorities, local self-government bodies, and civil society institutions to direct their activities towards effectively responding to climate change, taking into account the competence of specific public administration entities, and in collaboration with other national and international actors is determined. Furthermore, it is necessary to develop organizational and managerial, normative, and legal foundations of public administration entities' activities, particularly in the digitizing a wide range of services and mandatory training of public servants in communication with individuals with speech impairments.

Определены особенности и направления совершенствования административно-правового регулирования финансовых и экономических отношений в Украине. Новизна работы содержится в предложении отдельных новейших подходов в сфере нормативно-правового регулирования и организационно- управленческого обеспечения. Раскрыта сущность административно-правового регулирования и его элементов.
Administrative and legal regulation of financial and economic relations in Ukraine: features and areas of improvement
Keywords: адміністративно-правове регулювання; фінансові відносини; економічні відносини; напрямки вдосконалення; Україна; administrative and legal regulation; financial relations; economic relations; areas of improvement; Ukraine; административно-правовое регулирование; финансовые отношения; экономические отношения; направления усовершенствования; Украина